Current Dengue Virus Vaccine Developments and Future Directions - Govindaraj Anumanthan; Bikash Sahay; Ayalew Mergia (Viruses)
Dengue fever (DF), a leading arboviral disease globally, is caused by the Dengue virus (DENV) and represents a significant public health concern, with an estimated 390 million cases reported annually. Due to the complexity of the various dengue variants and the severity of the disease, vaccination emerges as the essential strategy for combating this widespread infectious disease. The absence of specific antiviral medications underscores the critical need for developing a Dengue vaccine. This review aims to present the current status and future prospects of Dengue vaccine development. Further, this review elaborates on the various strategies employed in vaccine development, including attenuated, inactivated, subunit, and viral vector vaccines. Each approach is evaluated based on its immunogenicity, safety, and efficacy, drawing on data from preclinical and clinical studies to highlight the strengths and limitations of each candidate vaccine. The current study sheds light on future directions and research priorities in developing Dengue vaccines. In conclusion, the development of a Dengue vaccine holds significant potential for reducing the global burden of DF. However, challenges remain in terms of vaccine safety, efficacy, delivery, and availability. Overcoming these challenges, coupled with advancements in vaccine technology, could lead to better control and prevention of Dengue, thereby enhancing public health and quality of life.